LncRNA FEZF1-AS1 Promotes Multi-Drug Resistance of Gastric Cancer Cells via Upregulating ATG5 - Gui, Zhifu; Zhao, Zhenguo; Sun, Qi; Shao, Guoyi; Huang, Jianming; Zhao, Wei; Kuang, Yuting (Frontiers in Cell and Developmental Biology, 2021)
Long non-coding RNAs (lncRNAs) play important roles in human cancers including gastric cancer (GC). Dysregulation of lncRNAs is involved in a variety of pathological activities associated with gastric cancer progression and chemo-resistance. However, the role and molecular mechanisms of FEZF1-AS1 in chemoresistance of GC remain unknown. In this study, we aimed to determine the role of FEZF1-AS1 in chemoresistance of GC. The level of FEZF1-AS1 in GC tissues and GC cell lines was assessed by qRT-PCR. Our results showed that the expression of FEZF1-AS1 was higher in gastric cancer tissues than in adjacent normal tissues. Multivariate analysis identified that high level of FEZF1-AS1 is an independent predictor for poor overall survival. Increased FEZF1-AS1 expression promoted gastric cancer cell proliferation in vitro. Additionally, FEZF1-AS1 was upregulated in chemo-resistant GC tissues. The regulatory effect of FEZF1-AS1 on multi-drug resistance (MDR) in GC cells and the underlying mechanism was investigated. It was found that increased FEZF1-AS1 expression promoted chemo-resistance of GC cells. Molecular interactions were determined by RNA immunoprecipitation (RIP) and the results showed that FEZF1-AS1 regulated chemo-resistance of GC cells through modulating autophagy by directly targeting ATG5. The proliferation and autophagy of GC cells promoted by overexpression of LncFEZF1-AS1 was suppressed when ATG5 was knocked down. Moreover, knockdown of FEZF1-AS1 inhibited tumor growth and increased 5-FU sensitivity in GC cells in vivo. Taken together, this study revealed that the FEZF1-AS1/ATG5 axis regulates MDR of GC cells via modulating autophagy.